Human nephron number, hypertension, and renal pathology. Issue 10 (15th November 2019) - Kanzaki, Go; Tsuboi, Nobuo; Shimizu, Akira; Yokoo, Takashi
Abstract: Recent studies have reported that total nephron number varies widely in human kidneys and some racial groups with low nephron number have a higher incidence of hypertension and kidney disease. Importantly, nephrogenesis normally reaches completion at about 34–36 weeks gestation, with no new nephrons formed for the lifetime in humans after this time. Although the loss of glomeruli varies among individuals due to aging, blood pressure, or additional inducers of kidney injury, much of the variation in nephron number is nowadays thought to be present at birth. According to the hyperfiltration hypothesis, this subsequent nephron loss results in compensatory hyperfiltration and/or hypertension of remaining glomeruli, thereby contributing to increased susceptibility to systemic hypertension. However, recent studies have suggested that the association between a low nephron number and systemic hypertension is not a universal finding. In most studies to date, nephron counts were performed on kidneys obtained at autopsy. Several recent studies have attempted to estimate nephron number in living human subjects, but further work is required to obtain accurate and precise estimates of nephron number using these noninvasive methods. Longitudinal studies in living humans have the potential to reveal associations between nephron number and hypertension/renal pathology.